An experimental investigation on thermal characteristics of sidewall fires in corridor-like structures with varying width. (May 2015) - Ji, J.; Fu, Y.Y.; Fan, C.G.; Gao, Z.H.; Li, K.Y.
Abstract: In order to study the effect of aspect ratios on thermal characteristics of sidewall fires in corridor-like structures, a set of small-scale experiments on sidewall fires was conducted in a model channel with adjustable width. The effects of channel widths on fire burning rates and the temperatures below the ceiling are analyzed. In the experimental-set width range, the changes for the fire burning rate, ceiling jet flame length and ceiling temperatures above the fire source are insignificant. However, when the width decreased to a certain value, the width has a significant effect on the ceiling temperatures in the downstream of fire source, especially near the opening end. The ceiling temperatures increases with the decreasing of channel width. Compared with the longitudinal direction, at the position with a certain distance transversely away from the fire source, the temperatures below the ceiling are more significantly affected by the channel width.